Cancer incidence and mortality in the Far Eastern Federal District (2013–2022) - V. P. Gordienko (Сибирский онкологический журнал)
The aim of the study was to assess the territorial patterns in cancer incidence and mortality among the population of the Far Eastern Federal District in the period 2013–2022. Material and Methods. Data from official reports of cancer services (form No 35, No. 7) processed using standard cancer statistics programs were presented. Results. In the east of the country, 31,822 new cancer cases were registered in 2022, which was 1.3 % more than in 2021. The average cancer incidence rate in males was 294.06 ± 5.05 per 100,000 (2020: 296.94 ± 4.66), with a decrease rate of 3.0 %. In females, the equivalent rate increased to 240.96 ± 5.73 per 100,000 (2020: 237.92 ± 6.26 per 100,000) with a rise of 6.3 %. Skin cancer was the most common malignancy (11.6 %) followed by trachea, bronchi, lung (11.5 %), breast (11.3 %) and colon (6.3 %) cancers. The percent of actively detected patients increased to 23.2 % (2013: 14.0 %) as did the index of accumulation of contingents – 7.3 (2013: 5.3). The number of patients with stage I–II cancer increased to 57.0 % (2013: 47.5 %), while the number of stage III-IV cancers decreased to 20.8 % (2013: 24.7 %). The number of morphologic studies (94.1 %) was lower than the average for RF (95.8 %). The proportion of patients registered for five or more years decreased to 57.2 % (RF: 58.2 %). The average cancer mortality rate in men was 174.99 ± 3.10 per 100,000 (2020: 181.76 ± 2.51 per 100,000). The average cancer mortality rate in women was lower than in men, being 91.34 ± 1.20 per 100,000 (2020: 93.71 ± 0.80о per 100,000). Cancers of trachea, bronchi and lung (20.0 %), stomach (8.9 %), colon (7.0 %) and breast (6.6 %) were the leading causes of mortality. Conclusion. The low level of active cancer detection did not significantly change the incidence rates during the study period. A greater volume of preventive measures with improvement of their quality will enable the primary health care system to detect cancer at early stages, form groups being at high risk for cancer development and, consequently, to reduce mortality rates. A prerequisite for improving medical care for cancer patients is the continuous training of professional staff and the use of modern diagnostic and treatment technologies.